Placenta as a source of human biochemical genetic markers - Tan, Soon Guan; Teng, Yao Sheng (Saraswati Press, 1977)
We have surveyed available methodologies and discussed the possible uses of placental enzymes as genetic markers. We have compiled a list of placenral enzymes demonstrable by the zyruugram technique.